Benefits of early intervention in family with children with Autism Spectrum Disorder - Cossio, Anelise do Pinho (2018)
The purpose of this paper is to present a review of research, covering the years 2005 to 2016, about benefits of Early Intervention (EI) for families with children with Autism Spectrum Disorder (ASD). Research has consistently documented that EI has influence in various domains of family life, particularly in the well-being and quality of life, in the development of competences, in the improvement of knowledge and information, and in the level of the engagement/involvement of the families in the process of support in the EI. The conclusion of this research allows us to understand that EI promote positive results for families in different life dimensions, thus allowing us to reinforce the importance of their effective involvement in all processes and moments of EI support. At the same time, reinforces the need for the adequacy and assessment of practices that results in benefits for families in EI.